THE POTENTIAL OF BAMBOO AS A SUSTAINABLE FOREST PRODUCT - Costa, Tiago; Lima, Lucas; Silva, Pedro (Journal of Selvicoltura Asean, 2025)
Bamboo is increasingly recognized as a sustainable forest product due to its rapid growth, versatility, and potential for contributing to environmental conservation. As global concerns about deforestation, climate change, and resource depletion grow, bamboo presents an alternative material that is both eco-friendly and economically viable. However, there is still limited research on its full potential, particularly in terms of its environmental benefits and commercial applications. This study aims to explore the potential of bamboo as a sustainable forest product by evaluating its environmental benefits, economic feasibility, and various commercial uses. The research also examines how bamboo cultivation can contribute to sustainable forest management and biodiversity conservation. A mixed-methods approach was used, combining a literature review, field surveys, and interviews with bamboo industry experts. Data were collected from bamboo cultivation sites, assessing growth rates, carbon sequestration potential, and local economic impacts. Qualitative interviews provided insights into the challenges and opportunities within the bamboo industry. The study found that bamboo grows rapidly, sequesters significant amounts of carbon, and provides an income-generating opportunity for rural communities. Bamboo-based products, such as construction materials and textiles, are gaining popularity due to their eco-friendly nature. However, challenges remain in terms of market development and supply chain infrastructure. Bamboo has substantial potential as a sustainable forest product that can play a key role in environmental conservation and economic development. Future research should focus on scaling up bamboo cultivation and improving market access to maximize its benefits.